EXPRESSION OF GENDER IN ANTHROPOCENTRIC PROVERBS (ON THE EXAMPLE OF ENGLISH AND UZBEK PROVERBS) (Archive of Conferences, 2022)
The anthropocentric paradigm allows to investigate the role of the human factor in linguistics in line with research objectives. This in turn puts man at the center of linguistics. The current proposal is based on the principles of the anthropocentric paradigm, which analyzes the linguocultural aspect of anthropocentric proverbs, i.e., the evaluation and imagery of the human gender, and illustrates them with examples.